2010
DOI: 10.1097/dad.0b013e3181bad002
|View full text |Cite
|
Sign up to set email alerts
|

Acantholytic-Like Malignant Melanoma: An Unusual Morphologic Variant

Abstract: We report the case of a primary cutaneous melanoma with acantholytic-like changes in a 61-year-old man. Clinical and immunohistochemic features were similar to those of other superficial spreading with vertical growth melanomas. Histologically, intraepidermal and suprabasal bullous spaces were filled by isolated tumor cells, simulating acantholytic blisters. These findings could be explained by the presence of inflammation-related extracellular fluid. Two other cases with suprabasal discohesive atypical melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The key histological finding in the present patient is discohesion of the atypical melanocytes, although pemphigus‐like acantholysis of the epidermis adjacent to the melanoma has been previously reported in two other patients . Discohesive findings of atypical melanocytes similar to the present patient have been reported by Kartono and colleagues and Aneiros‐Fernández and colleagues who described three cases of melanoma with an intense and diffuse discohesion‐like acantholysis. The present case also showed discohesion of unequivocal melanocytes that expressed S100 protein and HMB‐45.…”
Section: Resultssupporting
confidence: 74%
“…The key histological finding in the present patient is discohesion of the atypical melanocytes, although pemphigus‐like acantholysis of the epidermis adjacent to the melanoma has been previously reported in two other patients . Discohesive findings of atypical melanocytes similar to the present patient have been reported by Kartono and colleagues and Aneiros‐Fernández and colleagues who described three cases of melanoma with an intense and diffuse discohesion‐like acantholysis. The present case also showed discohesion of unequivocal melanocytes that expressed S100 protein and HMB‐45.…”
Section: Resultssupporting
confidence: 74%
“…Aneiros-Fernández et al 6 proposed the term "acantholytic-like malignant melanoma" instead, as dyscohesive cells can be observed also in other variants of melanoma, including particularly pseudoglandular melanoma. Acantholytic/bullous changes in malignant melanoma in the absence of a concomitant bullous disorder have been rarely reported before.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In addition to these 6 patients, rare cases of melanoma arising in patients with epidermolysis bullosa or Hailey-Hailey disease have been described, 7,8 as well as 1 case of vesiculobullous metastatic melanoma. To the best of our knowledge, only 6 cases have been reported to date in patients without a concomitant bullous skin disorder.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Here, we present a case of a well-differentiated syringomatous carcinoma with solid carcinoma-like features. 3 Few case reports regarding syringomatous carcinoma and solid carcinoma have been published and this case is also rare in terms of the location and size of the tumor. A 63-year-old man presented with erythematous plaque on his lumbar region.…”
Section: Well-differentiated Syringomatous Carcinoma With Solid Carcimentioning
confidence: 91%
“…Although the pathogenetic mechanisms remain unknown, some propose that molecular and immunological failures involving E-cadherin and b-catenin are involved in forming bullae in MM. [1][2][3] Because the lesions in these cases seemed to be caused by shoe/foot friction, Vogt et al 4 suggested that bullae may form due to friction plus strong intraepidermal growth of MM cells. In our case, we speculate that everyday stimuli, such as face-washing and scratching, plus intraepidermal growth of MM cells, caused the bulla on the MM, like the case of Vogt et al However, further analysis of similar cases is needed to clarify the pathomechanism underlying bulla formation in MM.…”
mentioning
confidence: 99%